For (x^(1/x))'....
Let y=(x^(1/x))
ln y = ln (x^(1/x))
ln y = (1/x)lnx
(ln y)' = [(1/x)lnx]'
(1/y) y' = (1/x)(1/x) + (lnx)(-1/x^2)
y' = [(1/x^2) - (lnx)/(x^2)][x^(1/x)]
2006-10-05 15:15:14
·
answer #1
·
answered by bassbredrin 2
·
0⤊
2⤋
First the formula: d/dx(a^x) = (a^x)(lna)(dx/dx)
ln = Natural Log,
(d/dx) = Derivative with respect to x,
(dx/dx) = Derivative of x with respect to x
So...
d/dx(x^(1/x)) = (x^(1/x))(lnx)(-x^-2)
(1/x can be rewritten x^-1)
=(x^(1/x))(lnx)(1/x^2)
I think this is right. I hope I used the right formula. Hope this helps.
2006-10-05 22:20:20
·
answer #2
·
answered by gonzo_fan2007 2
·
0⤊
1⤋
you can use logarithmic differentiation.
x^1/x = y
ln x^1/x = ln y
1/x ln x = ln y
1/y dy/dx = -ln x/x^2 + 1/x^2
dy/dx = y (1/x^2 - lnx/x^2)
now y = x^1/x so sub that in
dy/dx = x^1/x (1/x^2 - lnx/x^2)
and then u can simplify or whatever if u want.
2006-10-05 22:19:32
·
answer #3
·
answered by Anonymous
·
1⤊
1⤋
x^(1-2x)
There is no natural log crap going on there. Why do you guys above make it harder than it really is? Doing all that unnessary stuff just leads to errors.
2006-10-05 22:24:23
·
answer #4
·
answered by x 5
·
0⤊
1⤋
x^(1/x)=e^(ln x/x)
d(e^(ln x/x)/dx = x^(1/x) * (1/x² - ln x/x²) = (1-ln x)x^(1/x - 2)
2006-10-05 22:17:51
·
answer #5
·
answered by Pascal 7
·
0⤊
1⤋